An investigation into the stability of the big-five in Germany - Konrad C. Schäfer (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2017)
This paper investigates the stability of the Big-Five personality traits based on the German Socio-Economic Panel (SOEP) from 2005, 2009, and 2013. The results indicate that the population means only show little variance over the eight year time frame. There is no link between age and mean-levels, and only minor changes of the mean-levels of the Big-Five over time for the working age population (25-64 years of age) in Germany. However, there are intra-individual changes which can partly be explained by adverse life events. They impact the Big-Five traits and thereby contradict the general finding of stability of the traits in the literature. Exploratory fixed effects wage estimations that exploit the intra-individual changes in the Big-Five find no significant effects for men but positive effects of agreeableness and conscientiousness on women's wages.
Keywords: J3; C18; 330; Non-cognitive skills; Big-Five; personality traits; wages; Germany